Rural service centre: making a strategy for sustainable development in Bodhgaya block, Bihar - Pintu Kumar, (National Geographical Journal of India, 2023)
The study of the spatio-functional structure of the area is an important aspect of the diffusion of service centres with a geographical understanding of socio-economic development and its strategy for planning. Service centres are nuclei of the socio-economic structure which play important role in the process of decentralization of its socio-economic activities and optimum distribution of resources within their own range to the threshold population. It has been also observed that many new service centres are being developed in the backward area with benefits to the SCs community. They play a very important role to reduce the gap of regional imbalances, and socio-cultural and economic development while interlinking services to rural-urban areas in the study area. Bodhgaya is not only an important destination for tourists from all around the world but also shares large composition of the scheduled castes population (35%) as recorded in the 2011 census which is the prime concern to policy planners. This research paper attempts to identify the new important rural services centres for spatial expansion and diffusion of development with a spatial focus on the development of the SC community. The study area has great potential to develop Mankosi, Gapha, Kalan, Mora Mardana, Atiya, Gafa Khurd, Turi Buzurg by 2031.